Low-dose interleukin 2 for the reduction of vascular inflammation in acute coronary syndromes (IVORY): protocol and study rationale for a randomised, double-blind, placebo-controlled, phase II clinical trial. Issue 10 (7th October 2022) - Sriranjan, Rouchelle; Zhao, Tian Xiao; Tarkin, Jason; Hubsch, Annette; Helmy, Joanna; Vamvaka, Evangelia; Jalaludeen, Navazh; Bond, Simon; Hoole, Stephen P; Knott, Philip; Buckenham, Samantha; Warnes, Victoria; et al.
Abstract : Introduction: Inflammation plays a critical role in the pathogenesis of atherosclerosis, the leading cause of ischaemic heart disease (IHD). Studies in preclinical models have demonstrated that an increase in regulatory T cells (Tregs), which have a potent immune modulatory action, led to a regression of atherosclerosis. The Low-dose InterLeukin 2 (IL-2) in patients with stable ischaemic heart disease and Acute Coronary Syndromes (LILACS) study, established the safety of low-dose IL-2 and its biological efficacy in IHD. The IVORY trial is designed to assess the effects of low-dose IL-2 on vascular inflammation in patients with acute coronary syndromes (ACS). Methods and analysis: In this study, we hypothesise that low-dose IL-2 will reduce vascular inflammation in patients presenting with ACS. This is a double-blind, randomised, placebo-controlled, phase II clinical trial. Patients will be recruited across two centres, a district general hospital and a tertiary cardiac centre in Cambridge, UK. Sixty patients with ACS (unstable angina, non-ST elevation myocardial infarction or ST elevation myocardial infarction) with high-sensitivity C reactive protein (hsCRP) levels >2 mg/L will be randomised to receive either 1.5×10 6 IU of low-dose IL-2 or placebo (1:1). Dosing will commence within 14 days of admission. Dosing will comprise of an induction and a maintenance phase. 2-Deoxy-2-[fluorine-18] fluoro-D-glucose ( 18 F-FDG) positron emission tomography/CT (PET/CT) scans will be performed before and after dosing. The primary endpoint is the change in mean maximum target to background ratios (TBRmax ) in the index vessel between baseline and follow-up scans. Changes in circulating T-cell subsets will be measured as secondary endpoints of the study. The safety and tolerability of extended dosing with low-dose IL-2 in patients with ACS will be evaluated throughout the study. Ethics and dissemination: The Health Research Authority and Health and Care Research Wales, UK (19/YH/0171), approved the study. Written informed consent is required to participate in the trial. The results will be reported through peer-reviewed journals and conference presentations. Trial registration number: NCT04241601 .